2022
DOI: 10.1186/s12870-022-03635-4
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping and identification of genes associated with the resistance to Acanthoscelides obtectus in cultivated common bean using a high-density genetic linkage map

Abstract: Background Common bean (Phaseolus vulgaris L.) is an important agricultural product with large nutritional value, and the insect pest Acanthoscelides obtectus (Say) seriously affects its product quality and commodity quality during storage. Few researches on genes of bruchid resistance have investigated in common bean cultivars. Results In this study, a bruchid-resistant cultivar black kidney bean and a highly susceptible accession Longyundou3 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…Orthologs of the APA locus are present in tepary bean and transgenic azuki beans with tepary α ‐amylase inhibitor genes providing functional inhibition of insect α ‐amylases (Mirkov et al., 1994; Yamada et al., 2001). High resolution mapping of resistance to A. obtectus in a common bean recombinant inbred line population identified Phvul.006G003700 in the P. vulgaris v1.0 genome (Phvul.007G119178 in v2.1 P. vulgaris genome) as the causal gene which encodes an AAI‐LTSS (alpha‐amylase inhibitor [AAI], lipid transfer [LT] and seed storage [SS]) protein superfamily protein and speculated to function by inhibiting α ‐amylase (Li et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Orthologs of the APA locus are present in tepary bean and transgenic azuki beans with tepary α ‐amylase inhibitor genes providing functional inhibition of insect α ‐amylases (Mirkov et al., 1994; Yamada et al., 2001). High resolution mapping of resistance to A. obtectus in a common bean recombinant inbred line population identified Phvul.006G003700 in the P. vulgaris v1.0 genome (Phvul.007G119178 in v2.1 P. vulgaris genome) as the causal gene which encodes an AAI‐LTSS (alpha‐amylase inhibitor [AAI], lipid transfer [LT] and seed storage [SS]) protein superfamily protein and speculated to function by inhibiting α ‐amylase (Li et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…For example, SparkGATK [ 36 ], a framework for DNA analysis, has been used to detect allele-specific expression genes in plants [ 37 ]. SparkBWA [ 38 ], a DNA sequence alignment tool, has been used in [ 39 ] as part of the analysis pipeline to construct a high-density genetic linkage map for the common bean and identify a gene resistant to the bruchid, as well as to analyze the growth plasticity of bacteria in [ 40 ].…”
Section: Related Workmentioning
confidence: 99%
“…Li et al. (2022) also mapped one QTL for bruchid resistance on Pv06 using a bruchid‐resistant black bean. However, this QTL was in a different physical position to that of Kamfwa et al.…”
Section: Introductionmentioning
confidence: 99%
“…Kamfwa et al (2018) mapped the APA locus on Pv04 and reported additional resistance QTL on Pv06 using an Andean population of recombinant inbred lines derived from a cross of AO-3A and Solwezi. Li et al (2022) also mapped one QTL for bruchid resistance on Pv06 using a bruchid-resistant black bean. However, this QTL was in a different physical position to that of Kamfwa et al (2018).…”
mentioning
confidence: 99%